Clustering and Routing Algorithms for Wireless Sensor Networks : Energy Efficiency Approaches - Kuila, Pratyay; Jana, Prasanta K (Boca Raton, FL : CRC Press, 2017)
"Wireless Sensor Networks have a wide range of applications in different areas. Their main constraint is the limited and irreplaceable power source of the sensor nodes. In many applications, energy conservation of the sensor nodes and their replacement or replenishment due to the hostile nature of the environment is the most challenging issue. Energy efficient clustering and routing are the two main important topics studied extensively for this purpose. This book focuses on the energy efficient clustering and routing with a great emphasis on the evolutionary approaches. It provides a comprehensive and systematic introduction of the fundamentals of WSNs, major issues and effective solutions."--Provided by publisher.
chapter 1 Introduction / Pratyay Kuila Prasanta K. Jana -- chapter 2 WSN Applications / Pratyay Kuila Prasanta K. Jana -- chapter 3 A Survey / Pratyay Kuila Prasanta K. Jana -- chapter 4 Approximation algorithms for clustering / Pratyay Kuila Prasanta K. Jana -- chapter 5 CenffiIized Algorithms / Pratyay Kuila Prasanta K. Jana -- chapter 6 Metaheuristic Approaches / Pratyay Kuila Prasanta K. Jana -- chapter 7 Distributed Algorithms / Pratyay Kuila Prasanta K. Jana -- chapter 8 Fault Tolerant Algonthms / Pratyay Kuila Prasanta K. Jana -- chapter 9 Unequal clustering and mobile sink-based routing algorithms / Pratyay Kuila Prasanta K. Jana.
Keywords: Fuzzy algorithms; Wireless sensor networks; Algorithms & Complexity; Digital & Wireless Communication; Networks; COMPUTERS / Networking / General; MATHEMATICS / Arithmetic